2012
DOI: 10.1371/journal.pone.0032443
|View full text |Cite
|
Sign up to set email alerts
|

[11C]flumazenil Binding Is Increased in a Dose-Dependent Manner with Tiagabine-Induced Elevations in GABA Levels

Abstract: Evidence indicates that synchronization of cortical activity at gamma-band frequencies, mediated through GABA-A receptors, is important for perceptual/cognitive processes. To study GABA signaling in vivo, we recently used a novel positron emission tomography (PET) paradigm measuring the change in binding of the benzodiazepine (BDZ) site radiotracer [11C]flumazenil associated with increases in extracellular GABA induced via GABA membrane transporter (GAT1) blockade with tiagabine. GAT1 blockade resulted in sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…The elimination half-lives of these two drugs is similar at approximately 1.5e2.0 h in fasting subjects. The 15 mg dose of tiagabine study was chosen because it could be administered as standard tablet doses, is very similar to the 16 mg used in a PET study by Frankle et al (2012) and is identical with that used in several ongoing imaging studies by our group (Muthukumaraswamy et al, 2013b;Stokes et al, 2014) which have shown that GABA levels are increased.…”
Section: Design and Participantsmentioning
confidence: 99%
“…The elimination half-lives of these two drugs is similar at approximately 1.5e2.0 h in fasting subjects. The 15 mg dose of tiagabine study was chosen because it could be administered as standard tablet doses, is very similar to the 16 mg used in a PET study by Frankle et al (2012) and is identical with that used in several ongoing imaging studies by our group (Muthukumaraswamy et al, 2013b;Stokes et al, 2014) which have shown that GABA levels are increased.…”
Section: Design and Participantsmentioning
confidence: 99%
“…The low dose, which caused the same peripherally detected sympatholytic effects as the high dose, was not expected to reach significant a 2C -AR occupancy. The sedative and sympatholytic effects of dexmedetomidine are primarily mediated via the a 2A -AR subtype (Bucheler et al, 2002;Gertler et al, 2001). In experimental animals, the sedative effects of dexmedetomidine and the dexmedetomidine-induced reductions in noradrenaline release in the brain follow very similar dose-response patterns; dexmedetomidine has been found to reduce noradrenaline turnover in the brain, an effect which is absent in knock-out mice devoid of a 2A -ARs (L€ ahdesm€ aki et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine is a potent a 2 -AR agonist that is clinically used as a sedative-anesthetic agent (Gertler et al, 2001). Dexmedetomidine infusion causes a decrease in blood pressure and heart rate, which is thought to be the result of activation of autoinhibitory a 2A -ARs in the CNS, causing decreased sympathetic nervous system activity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 C]flumazenil, and [ 11 C]Ro15-4513 as a PET ligand with high affinity for α5-subunit-containing GABA A receptors with detecting either small changes 38 or markedly reductions 39 . These differences might also be explained by [ 11 C]flumazenil acting as a weak partial agonist and [ 11 C]Ro15-4513 being a partial inverse agonist at the benzodiazepine binding site 2 .…”
Section: Pet Radiotracers That Have Enabled Imaging Of Neurotransmmentioning
confidence: 99%